The Way We See Others in Intercultural Relations: The Role of Stereotypes in the Acculturation Preferences of Spanish and Moroccan-Origin Adolescents - Urbiola, Ana; López-Rodríguez, Lucía; Sánchez-Castelló, María; Navas, Marisol; Cuadrado, Isabel (Frontiers in Psychology, 2021)
Although the relationship between stereotypes and acculturation preferences has been previously studied from the majority perspective among adults, the perspective of adolescents and minority groups is understudied. This research analyzed the contribution of four stereotype dimensions (i.e., morality, immorality, sociability, and competence) to the acculturation preferences of Spanish adolescents and adolescents of Moroccan-origin, the moderating role of stereotypes in intergroup acculturation discrepancies, as well as the interaction of stereotypes with acculturation perceptions on acculturation preferences. A sample of 488 Spanish adolescents and 360 adolescents of Moroccan-origin living in Spain, from 12 to 19 years old, reported how moral, immoral, social, and competent they perceive each other to be. Spanish adolescents reported their perception about how Moroccan youth were acculturating in terms of maintaining their original culture and adopting the host culture, and their acculturation preferences in the same dimensions. Adolescents of Moroccan-origin reported to what extent they were maintaining their original culture and adopting the host culture, their acculturation preferences, and their ethnic and national (Spanish) identity. Results showed that adolescents of Moroccan-origin reported more positive perceptions of Spanish youth than conversely. The perceived immorality of the outgroup was important for understanding the preferences for adopting the host culture of both groups, but in the opposite direction. The four stereotype dimensions modulated the majority-minority discrepancies in preferences for cultural adoption. An analysis of the interaction between stereotypes and perceived adoption on acculturation preferences showed that when Spanish adolescents perceived that Moroccan youth were not adopting the Spanish culture, perceived morality and sociability played a role in their preferences for adoption. The less moral and sociable Moroccans were perceived, the more preference for cultural adoption. These findings support the importance of considering stereotypes in acculturation studies with majority and minority groups, as well as the relevance of including these perceptions in interventions aimed at improving intercultural relations.